An Analysis of English Vowels Pronunciation by The Third Semester Students of Pohuwato University - Hisasmaria (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
This research is about an analysis of English vowels pronounciation made by the third semester students of Pohuwato University. The researcher focused on the pronounciation of English pure vowels. This research investigated the types of error in English vowels pronunciation and to find out the common error in English vowels pronunciation made by the third semester students of Pohuwato University. This research was descriptive qualitative. The sample of the research was 20 students from the third semester students of Pohuwato University. The instruments used were test and recordings. The data analysis showed that most of the third semester students’ error pronunciation is substitution, for example the word improve /ɪm’pru:v/ the students pronounced /ɪm’pro:v/. It means that the vowel /u:/, is substituted by vowel /o:/. The second is insertion, for example the word simple /’sɪmpl/ the students pronounced /sɪmpel/. It means that there is an addition of vowel /e/. The third is ommision, for example the word update /ʌpdeɪt/, /ʌp’deɪt/ the students pronounced /apdet/, it can be stated that the vowel /ɪ/ is ommited. The most common error English vowel pronunciation made by the third semester students of Pohuwato University is substitution.